Exchange rates and market microstructure - the case of Guyana - Khemraj, Tarron...[et al.] ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Uses monthly data from March 2001 to December 2007 to test the Evans and Lyons (2002) model in the Guyanese foreign exchange market. Extends the basic model in Evans and Lyons (2002) by testing an alternative specification that includes risk.